Deltas: New paradigms - Carlos Zavala; Mariano Arcuri; Agustin Zorzano; Valentín Trobbiani; Antonela Torresi; Ainara Irastorza (The Depositional Record, 2024)
Abstract Deltas are deposits directly accumulated by land‐generated gravity flows in a standing body of water. The paradigm of deltaic sedimentation has dramatically changed during recent years, from the popular very simplified ternary models of marine littoral deltas towards more realistic and comprehensive models, considering the importance of sediment‐laden river discharges. Ternary delta models were designed for clean rivers, where a stream flow drags the sediments. Depending on the basin dynamics, these littoral deposits can be modified, forming tidal‐dominated, wave‐dominated or fluvial‐dominated littoral deltas. In recent years, a new classification of delta systems was proposed, based on contrasting the salinity of the receiving water body with the bulk density of the incoming fluvial discharge. Rivers are highly dynamic systems, and their discharges can be very variable in terms of flow duration and sediment concentration. Additionally, the salinity of the receiving water body can exhibit significant variability, especially in closed lakes and epicontinental seas, ranging from freshwater to brines. This scenario allows the distinction of three major delta categories (hypopycnal, homopycnal and hyperpycnal deltas) which can be in turn subdivided, defining seven delta types. Hypopycnal deltas form when the bulk density of the incoming flow is lower than the density of the water in the basin, allowing the definition of three delta types, corresponding to hypersaline littoral deltas, marine littoral deltas and brackish littoral deltas. Homopycnal deltas form when the bulk density of the incoming flow is similar to the density of the water in the basin, defining a delta type termed homopycnal littoral deltas. Hyperpycnal deltas form when the bulk density of the incoming flow is higher than the density of the water in the basin, allowing the definition of three categories termed hyperpycnal littoral deltas, hyperpycnal subaqueous deltas and hyperpycnal fan deltas.